A Comparative Study of PCA and KPCA for Groundwater Quality Index Estimation - Abdelaziz, Shokry; Kheimi, Marwan; Eizeldin, Mohamed A. H.; Safi Ahmed, Hassan (Civil Engineering Journal, 2025)
Groundwater quality assessment is crucial for ensuring human welfare and promoting sustainable economic development. This study evaluates the effectiveness of linear Principal Component Analysis (PCA) and nonlinear Kernel PCA (KPCA) in developing a reliable Groundwater Quality Index (GWQI) for Qena, Egypt. Using ten hydrochemical parameters from seventy-three groundwater samples, we compare the performance of four kernel functions within the KPCA framework. The PCA-based GWQI classified 71.0% of samples as suitable for irrigation, closely aligning with the Wilcox Diagram classification (76.7%). In contrast, KPCA with linear, polynomial, sigmoid, and radial basis function kernels yielded suitability rates of 58.9%, 52.1%, 63.0%, and 58.9%, respectively. These values are consistent with USSL (53.4%) and Na% (53.4%) classifications. Notably, the sigmoid kernel in KPCA demonstrated stronger correlations with Key hydrochemical parameters, effectively capturing nonlinear data structures. These findings underscore the importance of accounting for nonlinearity in groundwater quality assessment and demonstrate the potential of KPCA to improve GWQI accuracy. This comparative analysis highlights KPCA’s superiority over PCA for nonlinear datasets, providing enhanced tools for groundwater management and more reliable quality evaluations.